Identifying and Prioritizing Ethical Challenges in Clinical Services of Patients With Confirmed COVID-19 in Iran's Hospitals - Mohsen Keshavarz; Zohrehsadat Mirmoghtadaie; Maliheh Ahmadian; Davood Rasouli (Journal of Medical Education and Curricular Development)
Aim Since COVID-19 has set the state of health of the country in an emergency, it is natural that in such circumstances, violation of some principles of professional ethics is inevitable. This study aimed to identify and prioritize ethical challenges in the clinical services of patients with confirmed coronavirus disease in Iran's hospitals. Design This study was a mixed method with an exploratory sequential design. Methods This study was done in 2 qualitative and quantitative phases. In the qualitative phase, a systematized review was conducted and in the quantitative phase, a questionnaire of 35 questions based on the results of Phase 1 was formulated and completed. Results The challenges related to the provider of clinical services (physicians and nurses), the recipients of clinical services (patients), and the organizational challenges had the most significant importance, respectively ( P  < .05, χ2 = 6.23).